Formation of Disaster Preparedness School Cadres in MTSN 3 Muaro Jambi - Oktarina, Yosi; Astaria, Wike; Sintia, Fina; Taqwa, Muhammad; Siska Siska (Jurusan Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2023)
Flood disasters have been a never-ending problem for people all over the world from the past, present and in the future. These disasters can be the result of natural events or the result of human activities and activities, and can even be caused simultaneously by nature and humans. MTSN 3 Muaro Jambi as one of the schools located in Jambi Province has a high potential for flood disasters. This school is at risk of flooding every year due to the overflow of the Batanghari river which causes flooding in the school. This service activity is partnered with MTSN 3 Muaro Jambi. This service activity aims to increase school preparedness in dealing with flood disasters, provide education about the concept of disaster preparedness schools, and increase awareness of the character of caring for the environment in students in a sustainable manner. The number of participants who took part in this activity were 100 students. Activities carried out in school classrooms. The series of activities in this service are the implementation of pre-tests, education about flood disasters which include the definition of floods, types of floods, factors that cause floods, flood prevention, post-disaster diseases, and clean and healthy living behavior. Based on the results of the evaluation, the participants felt enthusiastic about participating in the activity and after being given counseling there was an increase in students’ knowledge about disaster preparedness. This disaster preparedness school is the best alternative in reducing the impact of disasters because schools are an effective vehicle in providing the effect of exchanging information, knowledge and skills to the nearest community, especially to children because children are the most vulnerable group affected by disasters.